Gene polymorphism of interleukin 1 and 8 in chronic gastritis patients infected with Helicobacter pylori - Caleman Neto, Agostinho (BioMed Central, 2014)
BACKGROUND: Epidemiological investigations have indicated that Helicobacter pylori induces inflammation in the gastric mucosa regulated by several interleukins. The genes IL1B and IL8 are suggested as key factors in determining the risk of gastritis. The aim of this paper was to evaluate the association of gene polymorphism of interleukin-1 and interleukin-8 with chronic gastrits in H. pylori infected patients. A total of 60 patients underwent endoscopic procedure. Biopsy samples were collected for urease test, histopathological and molecular exams. The DNA of theses samples was extracted for detection of H. pylori and analysis of the genes mentioned above. Patients with gastritis had a higher frequency of H. pylori-positive samples. RESULTS: H. pylori was detected in 30/60 patients (50%) by PCR. As for polymorphism of interleukin 8 (-251) gene we observed a statistical difference when analyzed TA (p = 0.039) and TT (p = 0.047) genotypes. In the IL1B31 there was a statistical difference in TT (p = 0.01) genotype and in the IL1B-511 there wasn’t any statistical difference. CONCLUSION: Our results suggest a strong correlation between the presence of chronic gastritis and infection by H. pylori and that IL1B-31TT and IL8-251TT genotypes appear to act as protective factors against H. pylori infection while IL8-251TA genotype may comprise a risk factor for infection with this bacterium.